(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article provides information about the system of speech therapy effects carried out to eliminate dysarthria; the tasks of speech therapy work with dysarthric children, methods and techniques of correctional work. In addition, the clinical features of dysarthria, its forms and the main directions of the correctional process are analyzed, as well as effective methods and technologies for organizing speech therapy work are highlighted.